Políticas públicas globais de incentivo ao uso da energia solar para geração de eletricidade - Lamarca Junior, Mariano Rua (2012)
We will analyze in this work public policies to promote the use of renewable energy sources within a group of selected countries, which are the industrialized countries in the Annex B of the Kyoto Protocol, the emerging BRICS group of countries (Brasil, Russia, India, China and South Africa) and the USA, focusing on solar energy for electricity generation. Comparing the main energy policies that are being designed in this representative group of countries, we find that is currently under construction, supported by a portfolio of policies that we will identify in the research, revolutionary technological innovation systems as a means of generating electricity from solar energy. We will demonstrate that the changes underway in energy policies of the most diverse Nation-States, setting goals for the participation of renewables in their energy mix, represent a global process of policy convergence, and that societies are moving towards a new paradigm where the pursuit of sustainability plays a key role in the policy building process